Strategic Entrepreneurship and Innovation Application in The Different Hotel Industry Management Models - Pirie, Brian Scott (2014)
The hotel industry forms a part of the global tourism industry. This research describes the management models that are currently applied and specifically asks whether different management models stimulate or constrain strategic entrepreneurship and innovation. There are a very small number of industry articles that address these topics, and the governance or management model is not identified as an influence on the activity in either strategic entrepreneurship or innovation. The qualitative research is conducted by semi-structured interviews and the findings discussed and illustrated by comparison of key areas of innovation between the 4 models of management in practice currently.